Differential Pulse Polarographic Behavior and Quantification of the Flucloxacillin in Pure and Pharmaceutical Dosage Forms Using a Static Mercury Drop Electrode - Ramadan, Abdul Aziz; Mandil, Hasna; Saleh, Reham Abu (JOURNAL OF ADVANCES IN CHEMISTRY, 2018)
Differential pulse polarographic analysis (DPPA) by using static mercury drop electrode (SMDE) for quantification of flucloxacillin (FLUX) in pure and pharmaceutical dosage forms was studied. The optimum conditions for the polarographic signal were determined and a study was made of the different parameters affecting the electrochemical process. The best definition of the analytical signals was found in Britton–Robinson buffer (0.06 M) at pH 4.0 . Under the optimum conditions, liner calibration graph, Ip=f(CFLUX) was obtained in the concentration ranges of 0.1 mM (0.0494 ?g.mL-1) to 26 mM (12.8414 ?g.mL-1) at -940 to -1000 mV (versus Ag/AgCl) with relative standard deviations (RSD) did not exceed 2.4% for the concentrations of FLUX (0.0494 ?g.mL-1). Regression analysis showed a good correlation coefficient (R2=9998) between Ip and concentration over the mentioned range. The limit of detection (LOD) and the limit of quantification (LOQ) were to be 0.0040 and 0.0120 ?g.mL-1, respectively. The proposed method was validated for linearity, precision and accuracy, repeatability, sensitivity (LOD and LOQ), robustness and specificity. The developed method is applicable for the determination of FLUX in pure and different dosage forms in presence a same amount of amoxicillin (AMOX) with average recovery of 99.4 to 102.2 % and the results are in good agreement with those obtained by the HPLC reference method.